Framing News About Turkey in Albanian and Kosovo Online Newspapers: The Case of Lake Memorial About 2016 Coup Attempt in Turkey - Granit Ajdini (Online Academic Journal of Information Technology, 2023)
This research examines the language used in media articles with framing content against Turkey in the Balkans, specifically in Albania and Kosovo. Albanian national identity and the nationalism that arose following the breakup of the Ottoman Empire have periodically resurfaced throughout modern history. Today, Albanian nationalism can sever ties with modern Turkey, often portraying the past and present in a negative light. The study focuses on how Albanian media with a nationalist perspective covered the construction of a Turkish memorial in Tirana's park, which was intended as a symbol of friendship between the two countries and as a tribute to the martyrs of July 15th. A total of 69 news articles were analyzed using both quantitative and qualitative methods, and categories of news framing related to a nationalist perspective in the journalists' reporting were identified. The results showed that media outlets in both countries covered the event, but Kosovo media displayed a higher level of framing against Turkey, despite the fact that the event took place in Albania. This nationalist approach suggests that Turkey continues to be perceived as a geostrategic, political, and cultural threat to the Albanian nation in the Balkans.